The Complexation of the Anticancer Drug ThioTEPA with Methylated DNA Base Guanine: Combined Ab Initio and QTAIM Investigation. Issue 2 (12th February 2014) - Nikolaienko, Tymofii Yu.; Bulavin, Leonid A.; Sukhodub, Leonid F.
Abstract Non‐covalent complexes of methylated nitrogenous DNA base guanine (m9Gua) with 1 to 6 molecules of anticancer drug ThioTEPA (1, 1′, 1′′‐phosphorothioyltriaziridine) have been investigated by molecular modeling techniques (molecular docking and DFT geometry optimization), ab initio wavefunction calculations and the quantum theory of atoms in molecules (QTAIM). The accuracy of complex structures predicted by standard molecular docking techniques have been assessed by comparing them with ab initio calculations, and the most important differences have been discussed. Obtained stabilization enthalpies (kcal/mol) for the m9Gua⋅⋅⋅(ThioTEPA)n complexes with n=1…6 have been found to be −15.6, −26.5, −38.4, −49.6, −60.5 and −69.3 respectively. The non‐covalent interactions revealed by the QTAIM method have been shown to be a dominating factor responsible for the complex stability, with hydrogen bonds of NH⋅⋅⋅N type being the most important interactions in small (n=1 to 4) and CH⋅⋅⋅N bonds – in large (n=5, 6) complexes. The obtained results may help to understand ThioTEPA‐DNA interactions and clarify the mechanism of the drug action.